Oxidative Stability of a New Peanut Butter Bite Product - Pranav Kaushik Pidatala; Danielle Bellmer; William McGlynn (International Journal of Food Science)
Peanut butter continues to be a mainstay in the American diet, but in its current form, peanut butter lacks the convenience of other foods. A peanut butter bite snack food has been developed that is individually wrapped, high in protein, and made mostly from peanut butter. The target market for the product is the active, health-conscious segment of the population that wants a high-protein peanut butter snack that is easy to pack, carry, and eat. The objective of the current study was to evaluate the shelf life of peanut butter bites under different storage and packaging conditions and specifically to monitor oxidative stability of the samples over time. Peanut butter bite samples were prepared with three different levels of added antioxidant (vitamin E). Products were sealed in two different types of packaging (metallized polyethylene and plastic polyethylene) and were stored at two different temperatures to determine the rate of deterioration of the product under various conditions. Oxidative stability was evaluated using two different analytical methods (peroxide value and TBARS assay) to evaluate primary and secondary oxidation products over a six month time period. All treatments were conducted in triplicate. Results show that higher levels of vitamin E resulted in greater stability. As expected, oxidation proceeded more quickly under higher temperature storage conditions. A shelf stable individually wrapped peanut butter snack product may be appealing to a large audience and could result in an increase in the consumption of peanuts.